An Unusual Coronary Artery Complication after Surgery for a Complex Congenital Heart Disease: A Case Report - Zaher, MD, Zaher Faisal (International Journal of Innovative Research in Medical Science, 2021)
Background: Unexpected events in cardiac surgery may increase morbidity and mortality, which may be more complicated and difficult to manage especially in redo complex congenital heart surgery in children. This report presents a case of unusual coronary artery complication after redo surgery for a complex congenital heart disease. Case Presentation: A female baby with ventricular septal defect, transposition of great arteries and coarctation of the aorta, underwent coarctation repair and pulmonary banding in neonatal period then at one year old, she underwent arterial switch operation and ventricular septal defect repair. In the pediatric cardiac intensive care unit, she required high doses of vasoactive inotropic drugs and echocardiography revealed sever right ventricular dysfunction without significant gradients or shunts. Accordingly, a diagnostic cardiac catheterization was performed and the aortic angiography revealed that the right coronary artery was not inadvertently transferred into the neo -aortic root during the step of arterial switch operation. The surgeon declared that he came upon confounding factors during the intraoperative assessment, which led him to identify a single coronary artery. Immediate reoperation performed to translocate the non-transferred right coronary artery into the neo aortic root and postoperatively the case required extracorporeal membrane oxygenation till she stabilized, and she was discharged in an acceptable condition. Conclusion: Early diagnosis and management of any complications related to coronary artery during pediatric cardiac surgery could lower risk and achieve favorable outcome.